The radical roots of Adventism in the Peruvian highlands - Teel Junior, Charles Williams (1989)
Graceful Horsemen riding mighty steeds charging at windmills are the stuff of which great works of literature are made as well as not-so-great motion pictures. The scene comes alive with a sea of ​​downtrodden indigenous people and a handful of mixed-race bishops, judges, and masters, for there are the possibilities of an impressive plot. Even better if the environment includes colorful clothing, blue skies, arid plains, and a majestic mountain lake.